Pengembangan Bahan Ajar PAI dengan Model Pembelajaran Kooperatif Tipe Numbered Heads Together - Hafid , Moh.; Khoiriyah, Umi (Jurnal Pendidikan Islam Indonesia, 2018)
This Islamic Education Module contains learning plans, objectives, subject matter, steps of learning activities, assessment, worksheets and evaluations. Based on the responses and assessments that have been made, it can be concluded that the Islamic Education Module can help and facilitate the teacher in the learning process. During the group discussion activities, there was a tendency that the topic of the issues being discussed expanded so that many did not match the time specified. The advantages of using cooperative learning model numbered heads together are, a) Students who are taught with and in cooperative structures will obtain higher learning outcomes, b) Students who participate in cooperative learning will have higher self-esteem and motivation greater for learning.